2013
DOI: 10.1021/cm401278m
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Computational Study of Oxide Ion Conduction Dynamics in Sr2Fe2O5 Brownmillerite

Abstract: We report a detailed study of the dynamics of oxide ionic conduction in brownmillerite-type Sr 2 Fe 2 O 5 , including lattice anisotropy, based on neutron scattering studies of a large (partially twinned) single crystal in combination with ab initio molecular dynamics simulations. Single-crystal diffraction reveals supercell peaks due to long-range ordering among chains of corner-sharing FeO 4 tetrahedra, which disappears on heating above 540 °C due to confined local rotations of tetrahedra. Our simulations sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 31 publications
8
69
1
Order By: Relevance
“…33 Additionally, more recent neutron diffraction experiments on single crystals grown by the floating zone method have indicated that P bcm is indeed the preferred structure type for Sr 2 Fe 2 O 5 . 18,19 Furthermore, all of these recent experiments are supported by the aforementioned results of our ab initio calculations; the small energy difference between the P bcm and I2bm structures, however, indicate that intergrowths of the phases is not out of the question. In contrast to the ambiguity of Sr 2 Fe 2 O 5 , the structure of Ca 2 Fe 2 O 5 is well known to form in the P nma phase, 17 again in agreement with our theoretical results.…”
Section: A Polyhedral Rotation Definitionssupporting
confidence: 82%
“…33 Additionally, more recent neutron diffraction experiments on single crystals grown by the floating zone method have indicated that P bcm is indeed the preferred structure type for Sr 2 Fe 2 O 5 . 18,19 Furthermore, all of these recent experiments are supported by the aforementioned results of our ab initio calculations; the small energy difference between the P bcm and I2bm structures, however, indicate that intergrowths of the phases is not out of the question. In contrast to the ambiguity of Sr 2 Fe 2 O 5 , the structure of Ca 2 Fe 2 O 5 is well known to form in the P nma phase, 17 again in agreement with our theoretical results.…”
Section: A Polyhedral Rotation Definitionssupporting
confidence: 82%
“…where, N A is the Avogadro constant, 6.02×10 23 (mol -1 ); a is the lattice constant of a pseudo-cubic SCN (with 10mol%Nb doping) is 3.90 Å 35 . According to prior studies, Co-3d orbital and O-2p orbital tend to hybridize strongly in SCO systems 21,32 , producing a broad conduction band. The mean-free-path between hole scattering event is short to give a weak temperature dependence of mobility =e/m* 36 , where e is the charge of the charge carrier;  and m* are collision time and effective mass of the charge-carrier, respectively.…”
Section: Structural Illustration Of Oxygen Interstitials In Donor-dopmentioning
confidence: 86%
“…Furthermore, these ordered oxygen vacancies have also been considered as good candidates for anion intercalation such as O 2and Fwith a full occupation of the vacant sites to yield a simple perovskite structure [29][30][31] . Aukett et al further confirmed by Lorentzian broadening of the quasielastic neutron scattering spectrum that induced rotations of BO 4 by higher temperatures are a precondition for moving oxide-ion into tetrahedral layers from the octahedral layers 32,33 , creating oxideion conduction pathways and activating long-range diffusion at the interface between layers; the latter is thought to be the driving force for oxygen vacancies disorder and isotropic oxygen diffusion. was given in their original paper why ( ) was chosen as a point defect.…”
Section: The Rationale For the New Defect Chemistry Modelmentioning
confidence: 94%
“…For example, brownmillerite SrCoO 2.5 (SCO) can undergo polymorphic phase transition under electric field control and has resistive switching behavior. 5,[7][8][9][10] Brownmillerite SrFeO x (SFO) with similar structure of SCO has been extensively studied due to its promising application in the fields of electrodes of fuel cell, magnetic storage, redox reaction catalyst, [11][12][13][14][15] etc. In addition, partial substitutions of the B specie of ABO 2.5 produce complex brownmillerite oxides such as Ca 2 FeAlO 5 , Ca 2 FeCoO 5 , etc.…”
Section: Introductionmentioning
confidence: 99%